Romidepsin Used as Monotherapy in Sequence with Allogeneic Stem Cell Transplant in a Patient with Peripheral T-Cell Lymphoma. (7th July 2014) - Finn, Nicholas; Larouche, Jean-Francois
Abstract : Despite advances in the field, a clear treatment algorithm for most peripheral T-cell lymphoma (PTCL) subtypes remains to be defined. Generating reliable randomized data for this type of pathology remains a challenge because of the relative rarity of the disease and the heterogeneity of subtypes. Newer agents, such as the class-I selective histone deacetylase inhibitor romidepsin, have demonstrated efficacy and manageable toxicity in the relapsed and refractory setting. Whether novel agents should be used in conjunction with more conventional cytotoxic therapies or in sequence with a transplant strategy is unknown at this time. Here we report the successful use of romidepsin monotherapy as a bridge to allogeneic stem cell transplantation in a patient who had previously relapsed after several lines of conventional cytotoxic therapy for PTCL. Romidepsin provided the patient with sufficient disease control to proceed to transplantation while remaining in complete remission.